Correlation between microstructure and charge transport in poly(2,5-dimethoxy- p-phenylenevinylene) thin films - Choulis, Stelios A.; Sims, Marc; Tuladhar, Sachetan M.; Nelson, J.; Maher, R. C. (My University, 2007)
We report a study of thin films of poly(2,5-dimethoxy- p -phenylenevinylene) (PDMeOPV) prepared by a precursor route. Conversion at two different temperatures, namely, 120 and 185deg;C, produces partially and fully converted films. We study the structural, optical, and charge transport characteristics of these samples in order to relate transport properties to microstructure. Micro-Raman mapping and photoluminescence (PL) imaging reveal the existence of coarse, depth-averaged domains of around 50 μm in lateral extent, with more pronounced contrast for conversion at the higher temperature. The contrast in both micro-Raman and PL maps can be attributed to fluctuations in film density. Spectroscopic ellipsometry studies of the films indicate that the average film density is approximately 15% higher for conversion at the higher temperature. Time-of-flight photocurrent transients, recorded here in PDMeOPV films, are typically dispersive but yield hole mobilities in excess of 10-4 cm2 V s at modest applied fields (∼1.2× 105 Vcm) in the fully converted films. To our knowledge, these are amongst the highest reported mobility values for a poly (p -phenylenevinylene) derivative. Fully converted films, while yielding higher hole mobilities, exhibit a stronger dependence on electric field than partially converted ones. The higher mobility can be attributed to the almost complete conversion of the flexible saturated subunits within precursor chains to conjugated vinylene moieties at elevated temperature. This results in a correspondingly higher packing density, an improvement in intrachain transport, and a reduction in the smallest interchain hopping distance. We suggest that the stronger electric field dependence is due to the increasing influence of intermolecular electrostatic interactions with decreasing interchain separation. We propose that a greater proportion of chains in the fully converted films packs in a three-dimensional, interdigitated arrangement similar to that described previously for crystalline samples of PDMeOPV
Keywords: Thin films; Condensed matter